Randomized Double-blind Controlled Trial: Benefits of Lactobacillus reuteri in Chronic Functional Constipation Patients - Taolin Agustinus; Marcellus Simadibrata; Irsan Hasan; Hamzah Shatri (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Chronic functional constipation is a common problem that affects between 15-25% of the population and cause symptoms and disorders that creates discomfort, morbidity, and high costs for health care. Recently, the consumption of probiotics in treating chronic constipation in adults have been investigated. However, there are still limited and controversial evidences available from controlled trials. The aim of this study was to evaluate the effects of Lactobacillus reuteri (L. reuteri) in improving the Agachan constipation score, the number of L. reuteri in the feces and the fecal pH in the patients with chronic functional constipation.Method: A double-blind, placebo randomized controlled trial (RCT) was conducted in 40 adults (12 males/28 females with mean age 45.95 ± 16 years) affected by chronic functional constipation according to Rome III criteria. Patients were randomly assigned to receive a supplementation of L. reuteri or placebo for 4 weeks.Results: At week 4, the decrease in Agachan constipation score was from 17.00 to 8.00 with p 0.001, the increase number of L. reuteri was from 6.80 x 107 to 2.12 x 108 with p 0.001 and the decrease of pH feces was from 5.44 (SD 0.70) to 4.78 (SD 0.56) with p 0.001 in the L. reuteri group, otherwise in the placebo group there were no significant results in Agachan constipation score, the number of L. reuteri and fecal pH assessed.Conclusion: L. reuteri is more effective than the placebo group in improving the Agachan constipation score, increasing the number of L. reuteri in the feces and decreasing the fecal pH in adult with chronic functional constipation.